Development and evaluation of an in vitro cardiovascular model for determining impact of genetic variability in calcium handling on drug-induced cardiotoxicity - Kha, Michelle (My University, 2019)
Cardiotoxicity is evaluated throughout the process of drug discovery and development and is a leading cause of drug attrition during clinical trials. One of the major challenges includes the understanding of differential pharmacology responses in healthy and disease states. This can be improved by the development of human in vitro models and consideration of genetic variability in patients. In this thesis, a human induced pluripotent stem cell (hiPSC) line was developed with a heterozygous single nucleotide polymorphism (SNP) rs3766871 (G1886S) within a calcium handling gene, RYR2. This SNP is the second most common heterozygous SNP within RYR2 and has been associated with cardiac diseases. The SNP line was obtained by reverse transfection of hiPSCs using CRISPR/Cas9 and was validated by Sanger sequencing. Furthermore, an existing hiPSC line with a heterozygous knock-out within RYR2 was evaluated in this thesis. The heterozygous knock-out hiPSC line mimics the partial reduction of RYR2 expression observed in aging and heart disease. This line was differentiated into cardiomyocytes and characterized by FACS, ICC and Western blotting. In addition, impedance-based measurements were conducted as a surrogate of contractility to obtain functional data of amplitude and beat rate of the cardiomyocytes. Differentiation of these hiPSC lines into cardiomyocytes, followed by drug treatment, will allow the hiPSC-derived cardiomyocytes to act as in vitro cardiovascular safety models of genetic variability. This can help understanding of the impact of genetic variability and its role in drug-induced cardiotoxicity.
Keywords: Fysik; Physical Sciences